Проблема пріоритетних видів рухової активності чоловіків зрілого віку - Футорний, Сергій Михайлович; Futornyi, Sergey (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено актуальні питання вивчення пріоритетних видів рухової активності серед чоловіків зрілого віку. Відповідно до аналізу даних сучасної літератури та моніторингу Інтернет-ресурсів установлено, що на сьогодні провідними видами рухової активності серед чоловіків зрілого віку є біг, ходьба, скандинавська ходьба й плавання оздоровчої спрямованості. Вивчення вітчизняних і міжнародних наукових розробок із цього питання дало змогу представити коротку характеристику результатів досліджень, навести статистичні дані та сформулювати практичні рекомендації. The article is devoted to studying of priority types of motor activity among men of mature age. According to the analysis data of modern literature and monitoring of Internet resources we found that today the leading kinds of motor activity among men of mature age are running, walking, Nordic walking and fitness swimming. Objectives of research: – analysis of the data scientific and methodical literature concerning the issues of priority kinds of motor activity for men of mature age; – generalize the domestic and world experience relative actuality question of chosen the kind of motor activity for men of mature age, as a leading factor in the direction of the formation not only of their own healthy lifestyle, and overall health. The study of national and international scientific research on the subject allowed submitting brief description results of research, statistical data and provided practical recommendations. Target orientation and its relevance in the implementation of chosen the kind of motor activity for men of mature age should include a range of awareness, understanding, willingness and desire to increase the level of their own health, its preservation and strengthening.
Тhe Question of Priority for Kinds of Motor Activity of Mature Age Men
Keywords: чоловіки зрілого віку; рухова активність; біг; ходьба; скандинавська ходьба; оздоровче плавання; здоров’я; men of mature age; physical activity; running; walking; Nordic walking; recreational swimming; health